Medical care for swimmers - Khodaee, M.; Edelman, G.; Spittler, J.; Wilber, R.; Krabak, B.; Solomon, D.; Riewald, S.; Kendig, A.; Borgelt, L.; Riederer, M.; Puzovic, V.; Rodeo, S. (Sports Medicine, 2016)
Swimming is one of the most popular sports worldwide. Competitive swimming is one of the most watched sports during the Olympic Games. Swimming has unique medical challenges as a result of a variety of environmental and chemical exposures. Musculoskeletal overuse injuries, overtraining, respiratory problems, and dermatologic conditions are among the most common problems swimmers encounter. Although not unique to swimming, overtraining is a serious condition which can have significant negative impact on swimmers` health and performance. This review article is an attempt to discuss various issues that a medical team should consider when caring for swimmers.